Doing Agile Right - Rigby, Darrell; Elk, Sarah; Berez, Steven (Ascent Audio, 2020)
For decades business leaders have been painfully aware of the huge chasm between their aspiration for a nimble, flexible enterprise and the reality of silos, sluggishness, and frustrated innovation. Today, agile is being hailed as the essential bridge across that chasm. Agile, say its enthusiasts, can transform your company, catapulting you to the head of the pack. Not so fast. In this clear-eyed and indispensable book, Sarah Elk and Steve Berez provide a much-needed reality check. They dispel the myths and misconceptions that have accompanied agile's growth-the idea that it can reshape your organization all at once, for instance, or that it should be used in every function and for all types of work. They affirm and illustrate that agile teams can indeed transform the work environment, make people's jobs more rewarding, and turbocharge innovation-but only if the method is fully understood and implemented the right way. Agile, done well, frees and facilitates vigorous innovation without sacrificing the efficiency and reliability essential to traditional operations. The authors break down how agile really works, show what not to do, and explain the crucial importance of scaling agile properly in order to get its full benefit. They then lay out a road map for leading the transition to a truly agile enterprise.
Online resource; Title from title page (viewed May 26, 2020)
Keywords: Business; Success in business; Agile project management; Affaires; Succès dans les affaires; Audiobooks